Effect of Characteristics and Entrepreneurial Orientation towards Entrepreneurship Competence and Crafts and Arts SMEs Business Performance in Makassar - Aisyah, St; Musa, Chalid Imran; Ramli, Anwar (International Review of Management and Marketing, 2017)
ABSTRACT This study was designed to test and analyze the characteristics and entrepreneurial orientation towards entrepreneurial competence and business performance. The population in this study were 117 owners / managers of SMEs crafts in the city of Makassar, with a rate of return of 79.49%. Convenience sampling technique is used with a total sample of 93 owners / managers. The results of the PLS Warp 5.0 analysis of provides evidence that the characteristics of entrepreneurs who are low in the opposite direction but it is significant to improving the entrepreneurial competence. High entrepreneurial orientation in the same direction and significant impact on improving the competence of the entrepreneurial characteristics of entrepreneurs who are low in the opposite direction and significant impact on business performance improvement. The owners or managers high autonomy are entrepreneurs strong desire to develop self-sufficiency in trying to have a significant impact on business performance. Low entrepreneurial competence in the opposite direction and no significant effect on business performance. Keywords: Characteristics, Orientation, Entrepreneurial Competence, Business Performance JEL Classification: M2